Phosphorylation-Dependent Targeting of Tetrahymena HP1 to Condensed Chromatin - Yale, Katerina (mSphere, 2016)
The evolutionarily conserved proteins related to heterochromatin protein 1 (HP1), originally described in Drosophila, are well known for their roles in heterochromatin assembly and gene silencing. Targeting of HP1 proteins to specific chromatin locales is mediated, at least in part, by the HP1 chromodomain, which binds to histone H3 methylated at lysine 9 that marks condensed regions of the genome. Mechanisms that regulate HP1 targeting are emerging from studies with yeast and metazoans and point to roles for posttranslational modifications. Here, we report that modifications of an HP1 homolog (Hhp1) in the ciliate model Tetrahymena thermophila correlated with the physiological state and with nuclear differentiation events involving the restructuring of chromatin. Results support the model in which Hhp1 chromodomain binds lysine 27-methylated histone H3, and we show that colocalization with this histone mark depends on phosphorylation at a single Cdc2/Cdk1 kinase site in the “hinge region” adjacent to the chromodomain. These findings help elucidate important functional roles of reversible posttranslational modifications of proteins in the HP1 family, in this case, regulating the targeting of a ciliate HP1 to chromatin regions marked with methylated H3 lysine 27. IMPORTANCE Compacting the genome to various degrees influences processes that use DNA as a template, such as gene transcription and replication. This project was aimed at learning more about the cellular mechanisms that control genome compaction. Posttranslational modifications of proteins involved in genome condensation are emerging as potentially important points of regulation. To help elucidate protein modifications and how they affect the function of condensation proteins, we investigated the phosphorylation of the chromatin protein called Hhp1 in the ciliated protozoan Tetrahymena thermophila. This is one of the first functional investigations of these modifications of a nonhistone chromatin condensation protein that acts on the ciliate genome, and discoveries will aid in identifying common, evolutionarily conserved strategies that control the dynamic compaction of genomes.